Violencia familiar y su relación con los nive les de Autoesti ma en mujeres del distrito de la Banda de Shilcayo. Enero - Mayo 2003 - Díaz Torres, Rachel (2004)
The present study was carried out in order to determine the relationship between family violence and levels of self - esteem in women in the Band District of Shilcayo January - May 2003. The methodology used in the present study was descriptive, Used the descriptive correlational design. The universe was constituted by 925 women belonging to the clubs of mothers aged 18 - 42 years, to whom the Murillo test was applied to determine the number of women who were raped in the last month prior to the survey, 448, representing 48.4%, to which the epi info statistical package was processed for the calculation of the sample, considering a sample of 130 women for the study, which was selected by systematic sampling. Total of 130 women, 89 obtained scores of 5 to 9 points with 68.4% and 41 women obtained scores of 1 to 4 points with 31.6o / o which showed that if there is large-scale family violence. Between 64.6% for those with inadequate self-esteem and 35.4o / o with adequate self-esteem. When the variables family violence and self-esteem levels were crossed, we found that 68.4% of mothers had higher scores Of violence (5-9 points), of which 85.5% present inadequate self-esteem. Of the 31.6% who have violence scores between 1 - 4 points, 80.5% have adequate self - esteem. These results show the highly significant association (P <0.05) between Family Violence and Self-esteem Levels, accepting the hypothesis presented in this study in which "A higher violence levels of self-esteem"